Understanding the impact of land use change on urban flood susceptibility mapping assessment: A review - Giofandi, Eggy Arya; Tjahjono, Boedi; Mahir Rachman, Latief (Brawijaya University, 2024)
Over the past few years, numerous urban areas have been identified in floodplains and coastal regions. These areas should be repurposed as water storage zones to enhance surface water infiltration. The escalating demand for land in flat areas adds complexity to the susceptibility of urban areas to flood hazards. The observation focuses on understanding how land use change influences urban flood susceptibility assessment. Several aspects assumed to have a significant relationship with the flood phenomenon include the impact of land use change, environmental health impact, modification of land typology, explanation of urban flooding, appropriate model for flood-prone assessment, current state of research, appropriate steps in decision-making in susceptibility areas, and challenges of the scenario-based flood-prone mapping model in the future. Additionally, the assessment aspect should consider the impact of land degradation resulting from land use change. Integrated measures are necessary to guide future studies aimed at improving ecological quality and restoring environmental health. The availability of free and open-source datasets facilitates conducting studies to support decision-making both locally and regionally.